Implementasi Sistem Inaportnet dalam Pelayanan Kapal di Terminal Sarana Citra Nusa Kabil pada PT. Snepac Shipping Batam - Putri Debora Veronika Nasution; Dirhamsyah Dirhamsyah; Fadiyah Hani Sabila (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This paper aims to provide in-depth insight into the complexity of handling ship arrivals and departures through the Inaportnet System by explaining how the system works, interactions between parties, and how the Inaportnet system helps improve the efficiency and smoothness of the shipping process at the terminal. This research was conducted at PT. Snepac shipping, daring the author’s pratek darat (PRADA) which began on January 17, 2024 to June 17, 2024. The datea source was obtained through primary data obtained directly from the Inaportnet system of PT. Snepac Shipping, with interviews conducted with managers and operational staff of PT. Snepac Shipping. As well as secondary sources, namely literature related to the title of this paper. The result of study lead to an in-depth understanding of the submission of ship arrival and departure permits at the Sarana Citra Nusa Kabil Special Terminal on the Inaportnet system. The involves the main focus is on how this system support document management, ship coordination, and port readiness, as well as a means of conneting ships and jetties for the implementation of activities at the port. In this context faciliating document management and port readiness which are integrated to support the smooth shipping process at the terminal.